Pembelajaran Daring Berbantuan Whatsapp Pada Matakuliah Metodologi Penelitian Pendidikan Fisika - Desy Kumala Sari; Syamsul Bahri; Merta Simbolon; Richardus F. Nikat; Pri Ariadi Cahya Dinata (Faculty of Teacher Training and Education, Musamus University, 2020)
Confront the pandemic COVID-19, online learning implemented at various level education. Online learning can be implemented with assistance Whatsapp application. This research was qualitative research with observe online learning activities. Conclution from this research was online learning assisted whatsapp can be alternative to teach non-exact material. The use of whatsapp application that was familiar to students make learning esier to implement. This online learning assisted whatsapp can also be applied in networks with slow internet access.